Immunomodulatory Effects of Dietary Seaweeds in LPS Challenged Atlantic Salmon Salmo salar as Determined by Deep RNA Sequencing of the Head Kidney Transcriptome - Palstra, Arjan P.; Kals, Jeroen; Blanco Garcia, Ainhoa; Dirks, Ron P.; Poelman, Marnix (Frontiers in Physiology, 2018)
Seaweeds may represent immuno-stimulants that could be used as health-promoting fish feed components. This study was performed to gain insights into the immunomodulatory effects of dietary seaweeds in Atlantic salmon. Specifically tested were 10% inclusion levels of Laminaria digitata (SW1) and a commercial blend of seaweeds (Oceanfeed®) (SW2) against a fishmeal based control diet (FMC). Differences between groups were assessed in growth, feed conversion ratio and blood parameters hematocrit and hemoglobin. After a LPS challenge of fish representing each of the three groups, RNAseq was performed on the head kidney as major immune organ to determine transcriptomic differences in response to the immune activation. Atlantic salmon fed with dietary seaweeds did not show major differences in performance in comparison with fishmeal fed fish. RNAseq resulted in ~154 million reads which were mapped against a NCBI Salmo salar reference and against a de novo assembled S. salar reference for analyses of expression of immune genes and ontology of immune processes among the 87,600 cDNA contigs. The dietary seaweeds provoked a more efficient immune response which involved more efficient identification of the infection site, and processing and presentation of antigens. More specifically, chemotaxis and the chemokine-mediated signaling were improved and therewith the defense response to Gram-positive bacterium reduced. Specific Laminaria digitata effects included reduction of the interferon-gamma-mediated signaling. Highly upregulated and specific for this diet was the expression of major histocompatibility complex class I-related gene protein. The commercial blend of seaweeds caused more differential expression than Laminaria digitata and improved immune processes such as receptor-mediated endocytosis and cell adhesion, and increased the expression of genes involved in response to lipopolysaccharide and inflammatory response. Particularly, expression of many important immune receptors was up-regulated illustrating increased responsiveness. NF-kappa-B inhibitor alpha is an important gene that marked the difference between both seaweed diets as Laminaria digitata inhibits the expression for this cytokine while the blend of seaweeds stimulates it. It can be concluded that the inclusion of seaweeds such as Laminaria digitata can have important modulatory effects on the immune capacity of Atlantic salmon resulting in a more efficient immune response.